Lightning signature as an index for the determination of the beginning of the Planting season in Nigeria (2004)
The discharge characteristics of a Franklin rod and a compound discharger with an insolated central point and surrounding points (a modified Franklin rod) has been investigated in the Laboratory and in the open atmosphere with a view to determine their effectiveness as lightning protectors. Analysis of the data showed that the compound discharger is about two and half times more effective as lightning protectors as compared to a typical Franklin rod with multiple ends. An aperiodic relationship between in (At V.. :/AVf) and m (dn/dt) has been observed instead of the speculated linear relationship. Investigation of the environment effects reveals that point- discharge current measurement from a point in a built discharge is an under-estimate.